Desenvolvimento de compósitos a partir das misturas de nanofibras celulósicas de eucalipto, fibras de bagaço de cana e casca de soja visando a purificação do biodiesel - Prado, Flávia Naves Ferreira do (2019)
The production of biofuels in Brazil, such as biodiesel is increasing, especially due to government incentives. In order to be commercialized, it must meet National Agency of Petroleum, Natural Gas and Biofuels (ANP) quality standards and, therefore, must be submitted to a purification process. The method of washing biodiesel with water, although efficient, generates a large amount of effluents. Dry-purification techniques, on the other hand, also have limitations, such as efficiency and cost, but they are environmentally friendly. It was proposed, in this research, to present an alternative route for the purification of biodiesel, through the development of low-cost filtering composites constituted by eucalyptus cellulose nanofibers and agroindustrial residues, such as sugarcane bagasse and soybean hull, both crude and chemically modified by acid regeneration and carboximethylation. The analysis performed to evaluate crude and filtered biodiesel quality were: acidity index, combined alkalinity, free glycerin content and refractive index. The characterization of the membranes was based on permeability, scanning electron microscope, energy dispersive X-ray spectroscopy, infrared spectroscopy by attenuated total reflection, contact angle, mechanical tests, surface area and porosity tests. The produced filters were mechanically very resistant, with rupture values with tension above 35 MPa. Mesmo em condições de baixa pressão, a permeabilidade dos compósitos, especialmente daqueles com composição incluindo resíduos regenerados, foi muito alta, com valores acima de 15096,00 L h-1 m-2 bar-1. Even under low pressure conditions, permeability values of the composites, specially for those with composition including regenerated residues, were very high, with values above 15096.00 L h-1 m-2 bar-1. The mean pore diameter of the membranes after addition of agroindustrial residues was reduced. The filters selected as the most efficient to reduce acidity, alkalinity and free glycerin content were those constituted with cellulose nanofibers and the following agroindustrial residues: 20% of 28 mesh regenerated sugarcane, 5% of 28 mesh regenerated soybean hull and 5% of 35 mesh regenerated soybean hull. The biodiesel purified by those membranes met the tested quality standards of ANP. In conclusion, the product developed by this research was shown as a promise in the biofuel production scenario.